Mechanical characterization of Raw-Perlite Solid Bricks for use in construction - Burgos, Lucas Ramiro (2020)
In San Antonio de los Cobres located to the west of Salta, Argentine, the residents resort to the use of Adobe bricks to build their houses. Suchmasonry is made by the residents themselves using old building techniques whose principal material is clay. At present, this material turns out to bescarce in the region due to the growing demand. On the other hand, in the vicinity of the town, there are mining plants which extract perlitegenerating wastes of particles smaller than 150 microns. With a high-content of residues (70% by weight), raw solid bricks are elaborated with aCINVA-Ram compacting unit. The aim of the present research work is to analyze the possibility of replacing Adobe bricks with these new bricks.Such analyses will follow tests which comply with IRAM standards (official national standards body for the Republic of Argentine), such ascompression and flexion strength, absorption, capillary absorption and thermal conductivity tests. In conclusion, our results indicated that rawperlite brick studied had better physical properties than the Adobe bricks.